Optimal Growth, Coordination and Sustainability in the Spatial Economy - Jeroen C.J.M. van den Bergh; Peter Nijkamp (Tinbergen Institute, 1997)
Until recently, the interaction between environmental quality, economic activity and growth is predominantly considered in an a-spatial context. Traditional neoclassical growth theory following Solow/Swan has mainly addressed questions about environmental and resource limits to growth. Recently, much attention is also devoted to the environment-growth interface from an endogenous growth perspective. However, an important element that is missing in both the neoclassical and endogenous growth approaches is a multiregional perspective. The present theoretical study tries to present one of the first attempts to fill this gap. The analysis is based on a model of two interactive regions, with possible interaction between the regional environments via the global environment. The implications of this type of analysis are manifold. One is that endogeneity of growth is not only due to technology and knowledge formation but also to the effects of trade, resource scarcity and environmental degradation. Another implication is that a coordinated environmental policy of regions should address long-term sustainability, and take account of the positive technological and negative environmental dynamic externalities.
Keywords: 330; Regionale Wachstumstheorie; Umweltökonomik; Neue Wachstumstheorie; Grenzüberschreitende Umweltbelastung; Umweltpolitik; Optimales Wachstum; Nachhaltige Entwicklung; Theorie